Morphology of testes, spermatogenesis, sperm bundles, and spermatozoa of Kerria chinensis (Hemiptera: Kerriidae). Issue 5 (19th September 2018) - Seubparu, Lucksanaveejit; Nipitwathanaphon, Mingkwan; Wisoram, Wijit; Merritt, David; Ngernsiri, Lertluk
Abstract: The filamentous spermatozoa of scale insects (Hemiptera) are highly modified compared with those of typical insects. Here, we investigate the morphology of the testes, sperm bundles, spermatozoa, and spermatogenesis of the wingless Kerria chinensis (Mahdihassan) (Hemiptera: Kerriidae), a shellac-producing scale insect. Each testis contains two antiparallel groups of several hundred syncytial sperm bundles. In each spermatocyte cyst, 16 primary spermatocytes divide via inverted meiosis, resulting in 16 quadrinucleated spermatids, each having two euchromatic and two heterochromatic nuclei. During spermiogenesis, each spermatid produces two spermatozoa protruding out of the spermatid close to the two euchromatic nuclei and their tails then grow in opposite directions. In each cyst, the 32 spermatozoa form two sperm bundles lying in an antiparallel direction oriented to different ends of the testis. Each spermatozoon has three distinct regions, an apex, a filamentous region and a tail. The spermatozoa have long thread-like nuclear cores that occupy about one-fourth of the sperm body length, located primarily in the posterior half. At the anterior end of the spermatozoon is a translucent, swollen vesicle and a distal, densely-stained structure; a putative acrosome of a type not previously reported in the spermatozoa of scale insects.